Classical Encryption Techniques - Sharma, Ramandeep; Sharma, Richa; Singh, Harmanjit (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
This paper reviews some of the classical encryption and modern techniques which are widely used to solve the problem in open networked systems, where information is being received and misused by adversaries by means of facilitating attacks at various levels in the communication. In this paper the proposition of building the basics of classical encryption and modern techniques and the comparison has been done between each of them.